A fatal case of disseminated melioidosis in a diabetic patient: diagnostic challenges and atypical presentation - Zakariah, Siti Zulaikha; Mohd Kamaruzzaman, Nur Hannah; Abdul Aziz, Nurul Izzati; Ibrahim, Rosni; Damanyanti, Rinni; Kandasamy, Thenmalar (UPM, 2024)
In Malaysia, melioidosis is not a notifiable disease but has a high mortality rate, particularly in diabetic patients. Disseminated melioidosis can be fatal, with 16% to 37% of cases presenting with nonspecific symptoms, complicating early diagnosis. Some patients develop abscesses with or without bacteremia. We present a fatal case of disseminated melioidosis in a diabetic patient with vague initial symptoms. Remarkably, she exhibited low septic parameters, including a normal white blood cell count and low C-reactive protein levels, which masked the severity of the infection and delayed appropriate treatment. The absence of early radiological findings and specific laboratory tests further complicated the diagnostic process. This case underscores the necessity for heightened clinical awareness and the advancement of diagnostic tools, particularly in high-risk populations, to facilitate timely interventions and mitigate fatal outcomes.